Maternal Outcomes in Preeclamptic Patients Presenting to CMH, Abbottabad - Mughal, Farida; Moin, Sadaf; Iffat, Shazia; Muzaffar, Tabassum; Gandapur, Shallozan Khannum; Arif, Farwah (Indus Journal of Bioscience Research, 2025)
Objective: To determine the frequency of maternal outcomes in patients presenting with pre-eclampsia. Research Design: A descriptive study. Duration and Place of Study: This study was conducted at the Obstetrics and Gynecology Department, CMH Abbottabad, from August 2024 to February 2025. Methodology: A total of 180 women aged 18–40 years with singleton pregnancies beyond 20 weeks of gestation and diagnosed with preeclampsia (blood pressure ≥140/90 mmHg and proteinuria ≥300 mg/24 hours) were included. Women with a history of cardiac, renal, or neurological disorders were excluded. Maternal complications, including cesarean section, ICU admission, anemia, pulmonary edema, acute kidney injury, and HELLP syndrome, were documented. Results: The mean age of participants was 27.98 ± 3.02 years, mean gestational age was 32.66 ± 2.44 weeks, mean parity was 2.55 ± 1.24, and mean BMI was 24.58 ± 2.26 kg/m². Most patients belonged to low or middle socioeconomic status (92.2%) and urban areas (61.7%). Cesarean section was the most frequent maternal outcome (63.9%), followed by ICU admission (17.8%) and anemia (17.2%). Other complications included pulmonary edema (11.1%), acute kidney injury (8.9%), and HELLP syndrome (6.7%). Conclusion: Preeclampsia is associated with significant adverse maternal outcomes, particularly cesarean section and critical complications like ICU admissions.